Analisis Perbedaan Peak Expiratory Flow (PEF) Pada Atlet Olahraga Renang dan Lari - Kukuh Pambuka Putra; Angkit Kinasih; Ardi Purwa Nugraha (LPPM STIKES Guna Bangsa, 2019)
Background: Asthma is a chronic disease that can be found in all ages. Basic Health Research Data (RISKESDAS) 2013 shows the prevalence in Indonesia of 4.5%. Asthma affects the expiratory rate in the lungs. PEF is the maximum expiratory speed that can be achieved by a person, expressed in liters per minute (L / min) or liters per second (L / sec). PEF can be measured using PEF meter. PEF meter is a tool for measuring maximum expiratory speed. Aerobic exercise such as swimming and running is the recommended exercise for asthmatics. Objective: This study aims to study the differences in PEF in individuals who regularly exercise swimming and running. Method: This study is a comparative study. The subjects of this study were 20 athletes who actively sport swimming and 20 athletes who are active in running sport determined by purposive sampling technique. Data analysis using independent t test. Result: The results of the study using the independent t test sig.0,890 value which states the average value of PEF athletes pool and run the same. Conclusion: Based on the research the value of PEF athletes pool higher than the value of PEF athletes run